2003
DOI: 10.3758/bf03194828
|View full text |Cite
|
Sign up to set email alerts
|

What is “marked” in visual marking? evidence for effects of configuration in preview search

Abstract: Visual search for a conjunction target is facilitatedwhen distractor sets are segmented over time: the preview benefit. Watson and Humphreys (1997) suggestedthat this benefit involved inhibition of old items (visual marking, VM). We investigated whether the preview benefit is sensitive to the configuration of the old distractors. Old distractors changed their location prior to the occurrence of the new items, while also either changing or maintaining their configuration. Configuration changes disrupted search.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 25 publications
1
34
0
Order By: Relevance
“…Furthermore, despite reports that object and spatial working memory may be segregated in posterior regions (Gnadt & Andersen, 1988;Miller, Li, & Desimone, 1993), the superior parietal lobe specifically subserves the preview effect (Allen, Humphreys, & Matthews, 2008;Humphreys et al, 2004;Olivers, Smith, Matthews, & Humphreys, 2005), and this region has been shown to be implicated in both spatial and object working memory (Xu & Chun, 2006). Indeed, previous studies have demonstrated that changing the identities of the previewed distractors is disruptive to the preview benefit (Jiang, Chun, & Marks, 2002;Kunar, Humphreys, Smith, & Hulleman, 2003), and Emrich and colleagues (2010) have provided support for the involvement of nonspatial memory in inhibition during search. Thus, from this work alone, it is not clear that the spatial subsystem of VWM is what more heavily supports the preview benefit.…”
Section: Spatial Versus Object Working Memorymentioning
confidence: 98%
“…Furthermore, despite reports that object and spatial working memory may be segregated in posterior regions (Gnadt & Andersen, 1988;Miller, Li, & Desimone, 1993), the superior parietal lobe specifically subserves the preview effect (Allen, Humphreys, & Matthews, 2008;Humphreys et al, 2004;Olivers, Smith, Matthews, & Humphreys, 2005), and this region has been shown to be implicated in both spatial and object working memory (Xu & Chun, 2006). Indeed, previous studies have demonstrated that changing the identities of the previewed distractors is disruptive to the preview benefit (Jiang, Chun, & Marks, 2002;Kunar, Humphreys, Smith, & Hulleman, 2003), and Emrich and colleagues (2010) have provided support for the involvement of nonspatial memory in inhibition during search. Thus, from this work alone, it is not clear that the spatial subsystem of VWM is what more heavily supports the preview benefit.…”
Section: Spatial Versus Object Working Memorymentioning
confidence: 98%
“…Here, we suggest that capacity limits are reduced by encoding old items as a single group on the basis of their time, their common color (when they have a common color), and their configuration (see Kunar, Humphreys, Smith, & Hulleman, 2003, for evidence of configural effects in preview search). Grouped old items can be inhibited together, and search can be biased away from them and toward a new set.…”
Section: Discussionmentioning
confidence: 99%
“…If the masked shape change abolishes the preview effect then search in these two conditions should differ (see also Braithwaite & Humphreys, 2007;Donk, Agter & Pratt, 2009;Donk & Theeuwes, 2001;Donk & Verberg, 2004;Emrich et al, 2008;Fenske et al, 2004;Jiang, Chun & Marks, 2002, Kunar et al, 2003a, Kunar et al, 2003d, Kunar, Shapiro & Humphreys, 2006Osugi, Kumada, Kawahara, 2009, for examples of other preview experiments which do not include a HEB).…”
Section: Change Blindnessmentioning
confidence: 99%